Incidencia de las redes sociales y contenido audiovisuales en el comportamiento de los adolescentes del sector La Aurora del cantón El Empalme, año 2021 - Loor Zambrano, Melissa Yamilet (2022)
The objective of this research was to analyze the incidence of social networks and audiovisual content on the behavior of adolescents in the La Aurora sector, Cantón el Empalme. Initially, a bibliographical research was developed that allowed us to understand the behavior of adolescents in the face of social and audiovisual media in a general context to obtain greater criteria and scientific rigor. Through the elaboration and subsequent analysis of the methods, a survey was carried out with a sample of 189 adolescents from the Aurora sector, for which 168 were surveyed, in which it was concluded that adolescents are immersed in a virtual world and it is highlighted that the The most used social network to socialize among colleagues is Facebook. In this context, one advantage of these virtual systems is that through them you interact with teachers and friends on academic learning issues, as in the case of WhatsApp, but on the other hand, you receive sexual harassment and bullying.